Explore the Value of Dual Source Computer Tomography Automatic Tube Current Regulation in Reducing the Radiation Dose of CTA in Lower Extremity Vessels - Hu, Xin; Yu, Yi (Frontiers in Surgery, 2022)
Objective: Explore the value of dual source computer tomography automatic tube current regulation in reducing the radiation dose of CTA in lower extremity vessels. Methods: Total of 64 patients who underwent CTA examination of lower extremity arteries due to symptoms of foot ischemia in our hospital from February 2020 to December 2021 were included. The patients were divided into a control group (treated with fixed tube current technology) and an observation group (treated with automatic tube current regulation technology) according to the random number table, with 32 cases in each group. All patients underwent a dual source computer tomography scan. Control group: tube voltage 120kV, tube current 250mA; Observation group: tube voltage was 80kV, and reference tube current was 80-380 mA. Other scanning conditions of patients in the two groups were the same. CTDIvol, DLP and calculated SNR and CNR were recorded to obtain the ED. Results: The values of CTDIvol, DLP and ED in the observation group were lower than those in the control group (P<0.05). There was no significant difference in CT value, SD value, SNR value and CNR value of the femoral artery segment, popliteal artery segment and posterior tibial artery segment between the two groups (P>0.05). The image quality scores of patients in the control group were slightly higher than those in the observation group, but there was no statistical difference between the two groups (P>0.05). Conclusion: The application of dual source computer tomography automatic tube current regulation technology in lower extremity vascular CTA examination can automatically adjust the compensation output, which can achieve the output of different tube currents in different thicknesses, different densities, and different angles. On the premise of not affecting the image quality, the radiation dose during the scanning is reduced to the maximum extent, and the tested patients are reasonably protected.